Glycolysis/gluconeogenesis specialization in microbes is driven by biochemical constraints of flux sensing. Issue 1 (7th January 2022) - Schink, Severin Josef; Christodoulou, Dimitris; Mukherjee, Avik; Athaide, Edward; Brunner, Viktoria; Fuhrer, Tobias; Bradshaw, Gary Andrew; Sauer, Uwe; Basan, Markus
Abstract: Central carbon metabolism is highly conserved across microbial species, but can catalyze very different pathways depending on the organism and their ecological niche. Here, we study the dynamic reorganization of central metabolism after switches between the two major opposing pathway configurations of central carbon metabolism, glycolysis, and gluconeogenesis in Escherichia coli, Pseudomonas aeruginosa, and Pseudomonas putida . We combined growth dynamics and dynamic changes in intracellular metabolite levels with a coarse‐grained model that integrates fluxes, regulation, protein synthesis, and growth and uncovered fundamental limitations of the regulatory network: After nutrient shifts, metabolite concentrations collapse to their equilibrium, rendering the cell unable to sense which direction the flux is supposed to flow through the metabolic network. The cell can partially alleviate this by picking a preferred direction of regulation at the expense of increasing lag times in the opposite direction. Moreover, decreasing both lag times simultaneously comes at the cost of reduced growth rate or higher futile cycling between metabolic enzymes. These three trade‐offs can explain why microorganisms specialize for either glycolytic or gluconeogenic substrates and can help elucidate the complex growth patterns exhibited by different microbial species. Synopsis: Microbes face a series of fundamental trade‐offs that limit their ability to optimize simultaneously for both glycolytic and gluconeogenic growth. Lag times between glycolysis and gluconeogenesis show asymmetry in many microbes: a long lag in one direction, but a short lag in the other. Long lag times are caused by an inability to sense fluxes after nutrient shifts. With existing regulation, lag time asymmetry can only be overcome by reducing either growth rate or increasing futile cycling in metabolism. Abstract : Microbes face a series of fundamental trade‐offs that limit their ability to optimize simultaneously for both glycolytic and gluconeogenic growth.